2010
DOI: 10.1016/j.neuron.2010.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Neuroligin 1 Promotes Growth and Postsynaptic Differentiation at Glutamatergic Neuromuscular Junctions

Abstract: Precise apposition of presynaptic and postsynaptic domains is a fundamental property of all neuronal circuits. Experiments in vitro suggest that Neuroligins and Neurexins function as key regulatory proteins in this process. In a genetic screen, we recovered several mutant alleles of Drosophila neuroligin 1 (dnlg1) that cause a severe reduction in bouton numbers at neuromuscular junctions (NMJs). In accord with reduced synapse numbers, these NMJs show reduced synaptic transmission. Moreover, lack of postsynapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
255
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(272 citation statements)
references
References 63 publications
15
255
1
1
Order By: Relevance
“…Previously, we found that muscle (Mef2-Gal4-driven) expression of GFP-tagged Nlg1 lacking its C terminus (UAS-Nlg1∆Cyto GFP (ref. 12) , Fig. 1a) results in marked under-growth of NMJs (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previously, we found that muscle (Mef2-Gal4-driven) expression of GFP-tagged Nlg1 lacking its C terminus (UAS-Nlg1∆Cyto GFP (ref. 12) , Fig. 1a) results in marked under-growth of NMJs (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Nonetheless, severe deficits in the in vivo assembly of Drosophila NMJ synapses [11][12][13] were reported for mutants of Nrx-1 and Nlg1 (for domain organization, see Fig. 1a).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations